KERAPATAN DAN KELAS KEHADIRAN JENIS EHA (CASTANOPSIS BURUANA MIQ) DI BLOK LINDUNG TAHURA NIPA-NIPA KELURAHAN PUNGGALOBA KENDARI - Rosmarlinasiah, Rosmarlinasiah; Arif, Asrianti; Dinasyarah, Hasdiyati; Nur, Hafidah; Laksanani, Satya Agustina; Mando, La Ode Agussalim (MAKILA, 2024)
The Tahura Nipa-Nipa nature conservation area located in the city of Kendari has a type of Eha that is susceptible to disturbance. The research aimed to determine the density level of the Eha (Castanopsis buruana Miq) species at tree, pole, sapling and seedling level growth; knowing the presence class in the community (presence) and knowing the distribution pattern. The observation sample used the plotted path method with a sampling intensity of 1% and an entire sample area of 0.96 ha. The sample consisted of 3 transects each containing 8 plots (0.04 ha per plot), so the total sample was 24 plots. Transects were placed systematically, the distance between transects was 100 m, and the distance between plots within transects was 20 m. The results showed that the Eha tree density level was 107.29 trees/ha, the pole level was 200 trees/ha, the sapling level was 233.33 trees/ha, and the seedling level was 13229.166 trees/ha. The presence of Eha in the community at the tree, pole and seedling level is in the "Always Present" class (81%-100%). Meanwhile, the stake level and presence in the community is in the "Sometimes There" class (21%-40%). The distribution pattern of Eha at the tree level is clustered, while at the pole, sapling and seedling levels it is a regular pattern.